2021
DOI: 10.1190/geo2020-0389.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling extra-deep electromagnetic logs using a deep neural network

Abstract: Modern geosteering is heavily dependent on real-time interpretation of deep electromagnetic (EM) measurements. We present a methodology to construct a deep neural network (DNN) model trained to reproduce a full set of extra-deep EM logs consisting of 22 measurements per logging position. The model is trained in a 1D layered environment consisting of up to seven layers with different resistivity values.A commercial simulator provided by a tool vendor is utilized to generate a training dataset.The dataset size i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In these situations, the use of PDE solvers for forward modeling may not be a good choice because of the computational cost. Recently, it was shown that the DNN models could provide a good approximation of the electromagnetic geophysical logs [Alyaev et al, 2021, Shahriari et al, 2020a.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…In these situations, the use of PDE solvers for forward modeling may not be a good choice because of the computational cost. Recently, it was shown that the DNN models could provide a good approximation of the electromagnetic geophysical logs [Alyaev et al, 2021, Shahriari et al, 2020a.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…In this work, a DNN is utilized as the forward model during the real-time probabilistic inversion. We use the trained DNN described in Alyaev et al [2021]. The DNN model is trained on the dataset [ Alyaev et al, 2021] containing around seventy thousand samples, which are created using a high-fidelity physics-based simulator provided by the tool vendor [Sviridov et al, 2014].…”
Section: Problem Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…These traditional methods evaluate the inverse solution pointwise (i.e., for a given set of measurements), but they rarely provide a global representation of the inverse operator. To overcome this problem and approximate the full inverse function, it is possible to use Deep Learning (DL) methods (see, e.g., [9,10,11,12,13,14]), which allow to approximate complex mappings via a composition of linear and non-linear functions.…”
Section: Introductionmentioning
confidence: 99%